An elderly patient of formalin poisoning presenting with hematemesis - Shrestha, Umid Kumar; Sapkota, Subash; Thapa, Prakash (Journal of Advances in Internal Medicine, 2012)
DOI: http://dx.doi.org/10.3126/jaim.v1i2.6527 Journal of Advances in Internal Medicine 2012;01(02):64